2003
DOI: 10.1046/j.1467-8624.2003.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, Substance Use, and Deviant Behavior: Examining Separation and Family Conflict as Mediators

Abstract: This longitudinal study examined how separation and family conflict mediated the effects of two acculturation variables (English language use and generational status) on substance use (alcohol, tobacco, and marijuana use) and deviant behavior outcomes in a Mexican American high school age sample. Structural equation modeling indicated that separation was a significant mediator of the relationship between acculturation and alcohol use, tobacco use, and deviant behavior. Family conflict mediated the effects of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 76 publications
8
86
0
2
Order By: Relevance
“…Contrary to expectations, there was no association between the other four potential mediators (depressive symptoms, self-esteem, family stress, parent conflict) and either acculturation or alcohol use. Prior research has linked these factors to alcohol use among non-Latino college students (Baer, 2002), and one study found that family conflict mediated between acculturation and substance use among Mexican American high school students (McQueen et al, 2003). Additional research is needed to replicate these findings and identify other mediators of the relation between acculturation and alcohol use among Latina college students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to expectations, there was no association between the other four potential mediators (depressive symptoms, self-esteem, family stress, parent conflict) and either acculturation or alcohol use. Prior research has linked these factors to alcohol use among non-Latino college students (Baer, 2002), and one study found that family conflict mediated between acculturation and substance use among Mexican American high school students (McQueen et al, 2003). Additional research is needed to replicate these findings and identify other mediators of the relation between acculturation and alcohol use among Latina college students.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of Mexican American adolescents, family conflict mediated associations between acculturation and substance use (McQueen, Getz, and Bray, 2003). Other research indicates that conflict in Latino families may be associated with acculturation-related issues (Vega and Gil, 1999).…”
Section: Acculturation Gender and Alcohol Use: Potential Interveninmentioning
confidence: 94%
See 1 more Smart Citation
“…The nature of these connections within the family may also be a strong factor in health. Some studies have found that for Latinos, family conflict was related to increased emotional distress and other health risk behaviors (McQueen, Getz, & Bray, 2003;Tschann, Flores, Marin, Pasch, Baisch, & Wibbelsman, 2002). Others have argued that changes in the structure of the Latino family across generations may increase stress thus negatively affecting Latinos' mental health (Alegría, Mulvaney-Day, Torres, Polo, Cao, & Canino, in press).…”
Section: Social Connections For Latinosmentioning
confidence: 99%
“…Not surprisingly, the stress of the acculturation process can cause psychological and behavioral problems among adolescents. Among Hispanic-American adolescents, acculturation to the United States culture has been associated with an increased risk of tobacco, alcohol, and other drug use [2][3][4][5][6][7]. The association between acculturation and substance use probably involves several mechanisms, including the more individualistic and rebellious social norms for adolescents in the United States, loss or rejection of traditional Hispanic cultural norms such as familism [8,9], and the stress of navigating two cultures simultaneously and feeling marginalized from one or both of those cultures [10].…”
Section: Introductionmentioning
confidence: 99%